MIF promotes cell invasion by the LRP1-uPAR interaction in pancreatic cancer cells - Sun, Huizhi; Cheng, Runfen; Zhang, Danfang; Guo, Yuhong; Li, Fan; Li, Yanlei; Li, Yue; Bai, Xiaoyu; Mo, Jing; Huang, Chongbiao (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by high aggressiveness and a hypoxic tumour microenvironment. Macrophage migration inhibitory factor (MIF) is a hypoxia-related pleiotropic cytokine that plays important roles in cancer. However, its role in PDAC progression has not been fully elucidated. Here, we demonstrated that the spatial distribution of MIF and HIF1A was highly correlated, and that high MIF expression was associated with poor prognosis of PDAC patients. MIF knockdown impaired cell invasion, with a decrease in the expression of urokinase-type plasminogen activator receptor (uPAR). Although PLAUR transcript was not reduced, a uPAR endocytic receptor, low-density lipoprotein receptor–related protein 1 (LRP1), was upregulated at both the mRNA and protein levels after MIF knockdown. The LRP1 antagonist RAP restored uPAR expression and invasiveness. MIF attenuated the nuclear translocation of p53, a transcriptional regulator of LRP1. Furthermore, MIF downregulation blunted the growth of PDAC cell xenografts and inhibited cell proliferation under normoxia and hypoxia. Transcriptome analysis also provided evidence for the role of MIF in cancer-associated pathways. Collectively, we demonstrate a novel link between the two pro-invasive agents MIF and uPAR and explain how MIF increases PDAC cell invasion capability. This finding provides a basis for therapeutic intervention of MIF in PDAC progression.